Conductivity and applications of Li-biphenyl-1,2-dimethoxyethane solution for lithium ion batteries - 褚赓 刘柏男 罗飞 李文俊 陆浩 陈立泉 李泓 (Chinese physics B, 2017)
The total conductivity of Li-biphenyl-1,2-dimethoxyethane solution（Li_xBp（DME）_（9.65）, Bp = biphenyl, DME = 1,2-dimethoxyethane, x = 0.25, 0.50, 1.00, 1.50, 2.00） is measured by impedance spectroscopy at a temperature range from 0℃ to 40℃. The Li_（1.50）Bp（DME）_（9.65） has the highest total conductivity 10.7 m S/cm. The conductivity obeys Arrhenius law with the activation energy（E_（a（x=0.50））= 0.014 eV, E_（a（x=1.00））= 0.046 eV）. The ionic conductivity and electronic conductivity of Li_xBp（DME）_（9.65） solutions are investigated at 20℃ using the isothermal transient ionic current（ITIC） technique with an ion-blocking stainless steal electrode. The ionic conductivity and electronic conductivity of Li_（1.00）Bp（DME）_（9.65） are measured as 4.5 mS/cm and 6.6 mS/cm, respectively. The Li_（1.00）Bp（DME）_（9.65） solution is tested as an anode material of half liquid lithium ion battery due to the coexistence of electronic conductivity and ionic conductivity. The lithium iron phosphate（LFP） and Li_（1.5）Al_（0.5）Ti_（1.5）（PO_4）_3（LATP） are chosen to be the counter electrode and electrolyte, respectively. The assembled cell is cycled in the voltage range of 2.2 V-3.75 V at a current density of 50 mA/g. The potential of Li_（1.00）Bp（DME）_（9.65） solution is about 0.3 V vs. Li~＋/Li, which indicates the solution has a strong reducibility. The Li_（1.00）Bp（DME）_（9.65） solution is also used to prelithiate the anode material with low first efficiency, such as hard carbon, soft carbon and silicon.